MINAT MAHASISWA MENJADI AKUNTAN PUBLIK: MOTIVASI, PERTIMBANGAN PASAR KERJA DAN PENGETAHUAN: Beberapa Perguruan Tinggi Swasta di Palembang - Damayanti, Rika; Mulatsih, Endang Sri; Pratiwi, Nurul Mardiyyah; Aktarina, Destia; Fikriyansyah, Ahmad (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
IAPI indicates that Indonesia faces a deficiency of public accountants. The deficiency of specialists is essential to forecast expansion in the business sector. One of IAPI's objectives for the